BRAND AS AN UMKM ASSET: A BUSINESS DEVELOPMENT STRATEGY IN SIMPLE BEACH VILLAGE, MUARA GEMBONG SUB-DISTRICT, BEKASI DISTRICT, WEST JAVA - Gunawan Widjaja (Adisam Publisher, 2025)
Brand identity development is crucial for Micro, Small and Medium Enterprises (MSMEs) engaged in the tourism industry, especially in Sederhana Beach Village, Muara Gembong District, Bekasi Regency, West Java. This beach village has great potential in tourism due to its natural beauty and charming local culture. However, MSMEs in the village are often faced with challenges in building a strong and attractive brand, hindering their business growth. The research method used in this study was sourced from the literature. The results show that a strong and attractive brand can attract more tourists, create a distinctive identity associated with natural beauty and local culture, and facilitate collaboration and promotion of the village as a complete tourist destination. Suggested business development strategies include coordinated brand management among local MSMEs, investment in training and guidelines on brand development, and support from local governments and relevant agencies in the form of technical assistance, funds, and coaching programmes. By implementing solid brand-based business development strategies, MSMEs in Pantai Sederhana Village can increase revenue, achieve sustainable business growth, and provide economic benefits to the local community. This research makes a significant contribution to the development of MSMEs in the tourism sector, particularly in maximising the potential of beach villages through effective brand management.